The determinants that influencing currency depreciation in Malaysia / Nur Syazwani Ibrahim - Ibrahim, Nur Syazwani (Faculty of Business and Management, 2017)
The depreciation of currency in Malaysia becomes a serious issue in economic condition. As a researcher I have made research about currency in Malaysia with the US Dollar day by day. The currency depreciation becomes an anxiety among people lately because it will affect their spending for daily life. Today (13 November 2016) the exchange rate is RM4.3742 to 1 USD and this is the lowest amount within 17 years since Asian crisis. The depreciation of currency also created a bad financial condition in economic scenario. The opinion of each analyst is different about this issue. Some of analyst considered that the currency depreciation due to the falling of global oil prices and some others considered because the currency in China depreciated. This is because the stock market of China is now experiencing the worst decline since 20 years ago. At this year since June, shares of China declined sharply to 30%. This fall is big enough for a second largest economic power in the world. It directly affects the value of the ringgit as Malaysia have very close economic ties with China. Malaysia-China trade relations between both countries already existed for 40 years and would have adverse effects in the Chinese economy and will affect the value of the Malaysian ringgit as well. Due this problem, the people also should take other alternatives to get over this issue in order to manage their financial as well. In order to get over this issue, the government should play the important roles to unsure that the currency in Malaysia will be back as normal. So, the purpose of this research is to examine what are actually the determinants that influencing the currency in Malaysia.